2017
DOI: 10.1098/rsos.171214
|View full text |Cite
|
Sign up to set email alerts
|

Hearables: feasibility of recording cardiac rhythms from head and in-ear locations

Abstract: Mobile technologies for the recording of vital signs and neural signals are envisaged to underpin the operation of future health services. For practical purposes, unobtrusive devices are favoured, such as those embedded in a helmet or incorporated onto an earplug. However, these locations have so far been underexplored, as the comparably narrow neck impedes the propagation of vital signals from the torso to the head surface. To establish the principles behind electrocardiogram (ECG) recordings from head and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 20 publications
2
57
0
Order By: Relevance
“…Technical aspects related to PPG signal filtering and PR estimation from in-ear devices were addressed in two additional studies (Vogel et al, 2009;Tomita et al, 2018). A filtering approach, based on dual PPG signal acquisition in both ears and asynchronous noise removal, was proposed by Tomita et al and tested under various movement and exercise conditions (Tomita et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Technical aspects related to PPG signal filtering and PR estimation from in-ear devices were addressed in two additional studies (Vogel et al, 2009;Tomita et al, 2018). A filtering approach, based on dual PPG signal acquisition in both ears and asynchronous noise removal, was proposed by Tomita et al and tested under various movement and exercise conditions (Tomita et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…filtering, amplification, and noise reduction modules), directly integrated in in-ear devices or in post-processing systems, are often required to condition the acquired signals and improve accuracy (Venema et al, 2012;Budidha and Kyriacou, 2014). The energy consumption of optical in-ear device is mainly related to LED driving, analog-to-digital conversion, and microprocessor operations (Vogel et al, 2009). Additional energy costs can be attributed to the presence of wireless communication modules for data transmission to other devices (e.g.…”
Section: Measurement Of Physiological Parameters From the Ear Canalmentioning
confidence: 99%
“…Our study utilised a monaural setup in order to minimise both the time for technical setup and participants' inconvenience, however, this might have interfered with the quality of recordings. As shown in our recent work [46], in addition to one more degrees of freedom in ear-EEG recording, a binaural setup would also allow for the monitoring of other physiological parameters such as ECG and respiration [28].…”
Section: Discussionmentioning
confidence: 99%
“…Hearables are earphones that are equipped with additional functions such as for example wireless connection to a smartphone or sensors for medical monitoring. Three studies could be found in this regard [81][82][83]. One publication investigated the possibility to measure neuronal auditory evoked potentials in the auditory canal by means of such a system [81] with the objective to improve the adaptation of hearing aids in particular in complex hearing situations.…”
Section: Studies On Apps Regarding "Hearables"mentioning
confidence: 99%
“…According to the authors, the sensitivity depends on the position of the contacts. Two other studies measured physiological parameters such as for example the heart rate, EEG, and speech synchronous respiratory movements, with specifically developed hearables [82,83]. However, very complex signal processing strategies were necessary to identify the signals.…”
Section: Studies On Apps Regarding "Hearables"mentioning
confidence: 99%